Evaluasi Luas Tutupan Lahan Kota Pematangsiantar - Muhammad Hafidzh Sitompul; Pindi Patana; Rahmawaty Rahmawaty (Peronema Forestry Science Journal, 2015)
Since population growth and development activities affect the quality and quantity of Urban environment, it’s followed by the change of land cover and evaluate of land cover in Pematangsiantar from 2003 to 2013 by using of Geographic Information Systems (GIS) with ArcView GIS 3.3 software application. The results showed that during the period 2003-2013 land cover of Pematangsiantar  area decreased by 6.67% following development activities.  Especially in the District Siantar Marihat and Siantar Martoba.  Pematangsiantar is currently cover at 55.47%.Keywords :   Land Cover, Pematangsiantar City, GIS, ArcView GIS 3.3